2017
DOI: 10.1176/appi.ajp.2016.16050517
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Patient Preferences on Outcomes in the Predictors of Remission in Depression to Individual and Combined Treatments (PReDICT) Study

Abstract: Treatment guidelines that recommend either an evidence-based psychotherapy or antidepressant medication for nonpsychotic major depression can be extended to treatment-naive patients. Treatment preferences among patients without prior treatment exposure do not significantly moderate symptomatic outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
99
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 119 publications
(102 citation statements)
references
References 57 publications
3
99
0
Order By: Relevance
“…Brain-based measures of major depression are proving superior to clinical measures and patient preferences in signifying differential outcomes to depression treatments (7,8,10). Such measures may provide a basis for possible future algorithms for triaging subjects to the appropriate treatment, likely as a component within a multivariate approach to prediction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Brain-based measures of major depression are proving superior to clinical measures and patient preferences in signifying differential outcomes to depression treatments (7,8,10). Such measures may provide a basis for possible future algorithms for triaging subjects to the appropriate treatment, likely as a component within a multivariate approach to prediction.…”
Section: Discussionmentioning
confidence: 99%
“…The design of the Emory PReDICT study has been published previously (39), and the clinical results of the trial are published elsewhere (10). The overarching goal of PReDICT was to identify clinical and biological moderators of outcomes to CBT and antidepressant medication.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study evaluated data collected from the Emory Predictors of Remission in Depression to Individual and Combined Treatments (PReDICT) study, for which the rationale, methods, and design have been previously published (Dunlop et al, 2012; Dunlop, Kelley et al, 2017). The study was conducted through the Emory Mood and Anxiety Disorders Program in English-language clinics at Emory University and in Spanish-language clinic at Grady Hospital in Atlanta.…”
Section: Methodsmentioning
confidence: 99%
“…Dunlop et al reported that patients matched to their preferred treatment could achieve a higher rate of treatment completion than those who were mismatched [44].…”
Section: Discussionmentioning
confidence: 99%